Educational games: Transdisciplinary impact on learning and scientific outreach (Research, Society and Development, 2024)
This research aimed to assess the transdisciplinary impact of educational games, highlighting their effective implementation across various disciplines and school levels. Additionally, it sought to establish guidelines for educational adaptation, aligning game mechanics with pedagogical objectives and fostering innovation in educational game development. Based on publications from ENPEC XIII, the research underscored the importance of games in the educational context and scientific outreach, showcasing positive outcomes in the classroom. Games were explored as didactic tools in both formal and non-formal settings, with an emphasis on mediating the environment to promote interaction and experimentation. The theoretical analysis incorporated Gee's perspective on constructivist environments and Mayer's multimedia cognitive model. The methodology involved a meta-analysis of articles in ENPEC XIII, categorizing them into pedagogical practices and guidelines for evaluating educational games. Results highlighted the diversity of games, revealing applications across various disciplines. The conclusion emphasized the need for clear guidelines for the effective adaptation of educational games, stressing the importance of aligning game mechanics with educational objectives and conducting rigorous assessments to ensure their effectiveness in the educational process. The study encouraged dialogue among educators, developers, and experts to drive the creation of innovative and effective educational games.